2013
DOI: 10.4257/oeco.2013.1702.08
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Competition in Structuring Ant Communities: A Review

Abstract: Understanding the mechanisms that determine local patterns of diversity is among the primary goals of ecology. Among these mechanisms, competition is mentioned as the regulatory factor structuring biological communities, despite the fact that the concept is controversial in ecology. Myrmecologists, however, for the most part, view competition as one of the main factors structuring ant communities. Two hypotheses on the mechanisms underlining species coexistence have received support from empirical studies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Also, even though it is a quite small area (as mentioned above), the variety of habitats found within the area is such that one 'needs' to sample all places. Many studies have been published from this study area by our research group using this same method (see Rico-Gray, 1993;Díaz-Castelazo et al, 2010, 2013Rico-Gray et al, 2012;Sánchez-Galván et al, 2012).…”
Section: Sampling Ant-plant Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, even though it is a quite small area (as mentioned above), the variety of habitats found within the area is such that one 'needs' to sample all places. Many studies have been published from this study area by our research group using this same method (see Rico-Gray, 1993;Díaz-Castelazo et al, 2010, 2013Rico-Gray et al, 2012;Sánchez-Galván et al, 2012).…”
Section: Sampling Ant-plant Interactionsmentioning
confidence: 99%
“…Inter-and intra-specific competition among ants is considered one of the main mechanisms structuring local ant assemblages (Andersen, 1992;Parr et al, 2005;Hölldobler & Wilson, 2008;Soares, 2013). This strong role of competition possibly occurs because most ant species are central place foragers and have similar requirements (nesting site and food supplies), resulting in less overlapping of their foraging areas (López, Serrano & Acosta, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…played by behavioral dominance in the primary, and thus most important, trait dimension related to resource exploitation in ants supports the assertion that competition is a hallmark feature of ant ecology when it comes to explaining species coexistence. The importance of behavioral dominance as a central trait in ant ecology has been underscored by a large number of publications and numerous recent reviews (e.g., , Soares 2013.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently a contentious debate about the exact role of competition on the structure of ant communities and ant dominance hierarchies (Arnan et al, 2018). Evidence has shown that ant species exert an influence on other ant species in the vicinity of their nests and that they compete for high-value food resources, but the effects of this competition at the community level are unclear (Soares, 2013; Arnan et al, 2018). Also, factors such as high temperatures, invasive species, parasitoids, and dietary differentiation have been observed to alter the role of competition on the structuring of ant communities, thereby facilitating the coexistence of ants with different competitive abilities (Parr & Gibb, 2012; Cerdá, Arnan & Retana, 2013; Houadria et al, 2015).…”
Section: Introductionmentioning
confidence: 99%